2018
DOI: 10.21577/0100-4042.20170297
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Espacial E Sazonal Das Concentrações De Partículas Totais Em Suspensão E Elementos Metálicos Associados No Ar De Uma Cidade Do Sudeste Brasileiro

Abstract: SPATIAL AND SEASONAL EVALUATION OF CONCENTRATIONS OF TOTAL SUSPENDED PARTICLES AND ASSOCIATED METALLIC ELEMENTS IN THE AIR OF A SOUTHEASTERN BRAZILIAN CITY. The present study evaluated the concentrations of Total Suspended Particles (TSP) and associated metals in three distinct regions of Ribeirão Preto city (Center City, Campus and Airport) in the dry and rainy seasons. There were no significant differences (p < 0.05) in TSP and metals concentrations between the sampling sites, except for Cu, Cr and Zn. Seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The Mn concentrations in the rainfall are higher in the spring and winter, but lower in the summer and may be caused by changes in the source of pollutants that can be attributed to the wind direction, which has a seasonal effect (Cheng et al, 2011). An evaluation of total suspended particulates in urban areas in South-East Brazil concluded that Mn concentrations were significantly higher in the dry season and may have resulted from changes in the rainfall pattern (Machado et al, 2018).…”
Section: Metalmentioning
confidence: 99%
“…The Mn concentrations in the rainfall are higher in the spring and winter, but lower in the summer and may be caused by changes in the source of pollutants that can be attributed to the wind direction, which has a seasonal effect (Cheng et al, 2011). An evaluation of total suspended particulates in urban areas in South-East Brazil concluded that Mn concentrations were significantly higher in the dry season and may have resulted from changes in the rainfall pattern (Machado et al, 2018).…”
Section: Metalmentioning
confidence: 99%